Analysis of the Lead Time Distribution in multi-product systems with dedicated buffers. Issue 11 (2018) - Angius, Alessio; Colledani, Marcello
Abstract: Perishable products that deteriorate before leaving the production system are common in industry. The most classic example is the food industry but several cases can be found in semiconductor manufacturing, and in polymers forming processes. These systems often require the scrapping of parts whose lead-time has exceeded a certain threshold. Previous works have considered single-product systems and have shown that the size of the buffers and actions dedicated to improve the machine availability may strongly affect the percentage of scrapped parts. In this paper, we model the dynamics of this phenomenon in a multi-product system composed of two machines that are connected through dedicated buffers. Furthermore, the model allows the use of three different policies for the mixing of products. The main contribution is a method for the calculation of the lead time distribution of each product that can be used to determine the effective throughput of the system. The relevance of the method is shown by means of numerical results that provide important insights on the problem and show counterintuitive behaviors.